Communication that Saves: Improving the Resilience of Law Enforcement Families - Fu'ady, Muh Anwar (Proceedings Conference Psychology and Flourishing Humanity; Vol 2 No 1 (2025): Proceedings Conference on Psychology and Flourishing Humanity, 2026)
Law enforcement families are under considerable pressure due to the profession’s high risks, heavy workloads, and strict institutional demands. This pressure can lead to domestic conflicts and a decline in family relationship quality. Communication patterns are believed to be an essential protective factor in strengthening family resilience. This study aims to analyze the influence of communication patterns on family resilience among married law enforcement officers. This study used a quantitative approach involving 80 convenience sampling participants. The Walsh Family Resilience Questionnaire and the Revised Family Communication Pattern were used to measure family resilience and communication patterns. Data analysis was performed using simple regression with JASP version 0.19.2.0.  Communication patterns significantly affected family resilience (R = 0.509; R² = 0.259; p < 0.001). In particular, the conversation orientation dimension contributed positively and significantly to resilience (β = 0.582; p < 0.001), whereas conformity orientation had no significant effect (β = –0.031; p = 0.784). These findings confirm that open, honest, and supportive communication is a lifesaving strategy for law enforcement families to remain resilient in the face of professional pressures, whereas communication patterns that emphasize excessive conformity actually weaken family resilience. This study enriches the literature on family resilience in the context of high-risk professions while providing practical recommendations for law enforcement officers for effective communication training and preventive counselling for family development programs.